Search
 
Write
 
Forums
 
Login
"Let there arise out of you a band of people inviting to all that is good enjoining what is right and forbidding what is wrong; they are the ones to attain felicity".
(surah Al-Imran,ayat-104)
Image Not found for user
User Name: Noman
Full Name: Noman Zafar
User since: 1/Jan/2007
No Of voices: 2195
 
 Views: 1295   
 Replies: 5   
 Share with Friend  
 Post Comment  
Look at the beauty of the following theorem:
 
Theorem: 4 = 5

Proof:

-20 = -20
16 - 36 = 25 - 45
4^2 - 9*4 = 5^2 - 9*5
4^2 - 9*4 + 81/4 = 5^2 - 9*5 + 81/4
                        
Since (a-b)^2 = a^2  +  b^2  -  2ab
 

(4 - 9/2)^2 = (5 - 9/2)^2
 
Taking under root of both sides

4 - 9/2 = 5 - 9/2
4 = 5
 
 
 
It is fairly proved that 4=5, which our senses believe to be wrong.
 Reply:   You are good/
Replied by(Noman) Replied on (22/Nov/2007)

This theorem is for fun only, but thanks for discussing it in so detail.
and in fact during discussion u gave me other fun theorems as well.
and sacc_Pakistani keep it boy ;) after being so attached with MQM you started to adopt habits of Altaf as well, No matter what is the matter pass comments.
 
 Reply:   Re sorry princess, your approa
Replied by(princess_of_dhump) Replied on (22/Nov/2007)

let we assume that
a^2=b^2
means a=b (for argument only)

(-1)^2=(1)^2=1 this means -1=1 or 2=0 (adding one both side)
once 2=0 divide both by 2
gives 1=0
than multiply both side by any number
which will give every number equals zero (rubbish)
all rubbish

I ve seen such rubbish proves on many sites and emails all use some jugglery and comes to foolish results after inadequate use of square root. Please go through basics mathematics and be aware that

a^2=b^2 never ever means a=b

(4-9/2)^2=(5-9/2)^2
(-1/2)^2=(1/2)^2
 
 Reply:   princess dont mind - he is a m
Replied by(sacha_pakistani) Replied on (21/Nov/2007)

he can proof that dog is cat and can argue whole day on it, he is very sad person, u can imagine.
 
 Reply:   sorry princess, your approach
Replied by(Noman) Replied on (21/Nov/2007)

if a^2=b^2 then it is only possible
if a=b
above theorem is for values not for variables.
if both sides has same value, then no need to solve it, we can simple remove it from both sides as
if
2-a=2-b then it can be simplified as
a=b

similarly
(4-9/2)=(5-9/2)
can be written as
4=5
as -9/2 is canceling each other on both sides.

 
 Reply:   wrong
Replied by(princess_of_dhump) Replied on (20/Nov/2007)

dear there
a^2=b^2
never means a=b
however it means
either
a=b
or
a=-b
i repeat either of two nor both
so here true one is
(4-9/2)=-(5-9/2)
-1/2=-1/2
 
Please send your suggestion/submission to webmaster@makePakistanBetter.com
Long Live Islam and Pakistan
Site is best viewed at 1280*800 resolution